2010
DOI: 10.5194/acp-10-10321-2010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the impact of deep convection on reactive Volatile Organic Compounds in the upper tropical troposphere during the AMMA experiment in West Africa

Abstract: Abstract.A large dataset of reactive trace gases was collected for the first time over West Africa during the African Monsoon Multidisciplinary Analysis (AMMA) field experiment in August 2006. Volatile Organic Compounds (VOC from C5-C9) were measured onboard the two French aircrafts the ATR-42 and the Falcon-20 by a new instrument AMOVOC (Airborne Measurement Of Volatile Organic Compounds). The goal of this study is (i) to characterize VOC distribution in the tropical region of West Africa (ii) to determine th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 46 publications
(40 reference statements)
4
36
0
Order By: Relevance
“…Using aircraft measurements performed in the framework of the African Monsoon Multidisciplinary Analyses (AMMA) project, showed clear signatures of convective uplift of CO and aerosols into the tropical tropopause layer (TTL). Results from Bechara et al (2010) also pointed to convection as an explanation for observed enhancements of VOCs in the UT over West Africa. Moreover, Sauvage et al (2007b, c) and Barret et al (2010) demonstrated that convection leads to production of important amounts of NO x from lightning in the UT which subsequently leads to O 3 production downwind.…”
Section: Introductionmentioning
confidence: 82%
“…Using aircraft measurements performed in the framework of the African Monsoon Multidisciplinary Analyses (AMMA) project, showed clear signatures of convective uplift of CO and aerosols into the tropical tropopause layer (TTL). Results from Bechara et al (2010) also pointed to convection as an explanation for observed enhancements of VOCs in the UT over West Africa. Moreover, Sauvage et al (2007b, c) and Barret et al (2010) demonstrated that convection leads to production of important amounts of NO x from lightning in the UT which subsequently leads to O 3 production downwind.…”
Section: Introductionmentioning
confidence: 82%
“…3.2 and 3.3). In addition, Bechara et al (2010) observed O 3 mixing ratios in the range of 45 nmol mol −1 within the fresh MCS outflow during AMMA compared to 60 nmol mol −1 outside. As the MCS outflow ages, the O 3 composition in the MCS outflow may be affected both by photochemical O 3 production/destruction of uplifted precursors and mixing with the ambient air (Chatfield and Delany, 1990).…”
Section: Production Destruction or Mixing Of O 3 In The Mcs Outflow?mentioning
confidence: 93%
“…The AMMA SOP-2a2 campaign, carried out from 25 July to 31 August 2006, involved not only the German Falcon-20 and Russian M55 Geophysica research aircraft based in Ouagadougou, but also the French Falcon-20 and ATR-42 aircraft, and the British Facility for Airborne Atmospheric Measurements (FAAM) BAe-146 aircraft, all based further northeast in Niamey (13.5 • N, 2.1 • E) in Niger Ancellet et al, 2009;Saunois et al, 2009;Bechara et al, 2010;Law et al, 2010;Real et al, 2010;Reeves et al, 2010). Further downstream, in the Cape Verde region off the coast of West Africa, the NASA-AMMA program (NAMMA) examined the interaction between African Easterly waves (AEW) and the Saharan air layer (SAL) and their role in tropical cyclogenesis (Jenkins et al, 2008;Zipser et al, 2009;Cifelli et al, 2010).…”
Section: The Amma Sop-2a2 Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…PAN or HNO 3 ). The AFR air mass trajectories ( Figure 5) mostly originate from too far north to pick up substantial biomass burning, soil or lightning emissions of NO x (Richter and Burrows 2002;Yienger and Levy 1995), CO and NMHC (Bechara et al, 2010;Gros et al, 2004;Hao et al, 1996) from the north African savannahs (Figure 19), although an influence from these sources cannot be ruled out. The west African coastal cities of Dakar and Nouakchott as well as higher ship emissions from the north-east to easterly sectors, are also likely to influence NO y and NO x levels observed at Cape Verde.…”
Section: Greenhouse Gasesmentioning
confidence: 99%